Phylogeny, phylogeography, and conservation of a rediscovered gecko from the Galápagos Islands - Omar Torres-Carvajal; Paula A. Castaño; Enrique Rincón; Fernando Ayala-Varela; Karl Campbell; Wilson Cabrera; Francisco Moreno (PLoS ONE, 2025)
The rediscovery of species in iconic conservation sites like the Galápagos is eye-catching and can lead to quick and effective conservation actions. With 11 species occurring on most islands, Galápagos leaf-toed geckos (Phyllodactylus) are among the least known terrestrial vertebrates of the archipelago. Strikingly, reliable records of Phyllodactylus from Rábida Island prior to this study are limited to Holocene subfossils and a single photograph from 2012. Here we report the first vouchered specimens of Phyllodactylus from Rábida and present their phylogenetic and phylogeographic affinities with other gecko populations in the archipelago. Despite taxonomic uncertainty, we recognize Rábida gecko populations as a separate ESU within P. maresi, which also occurs in nearby islands (Santiago, Bartolomé, Mares), as well as in Marchena. Finally, we suggest that Rábida gecko populations benefited from the eradication of invasive rodents, which facilitated their rediscovery and the collection efforts reported here.